GE_GERICHTE P/9822/2012 vom 25. September 2012 - GE Cour de justice (2012)
; ADOLESCENT ; DÉTENTION PROVISOIRE ; PROLONGATION ; COMPÉTENCE RATIONE MATERIAE ; PROPORTIONNALITÉ | PPMin.27; PPMin.39; CPP.222;